Anti-angiogenic collagen fragment arresten is increased from 16 weeks' gestation in pre-eclamptic plasma. Issue 11 (November 2015) - Yong, Hannah E.J.; Murthi, Padma; Wong, May H.; Kalionis, Bill; Brennecke, Shaun P.; Keogh, Rosemary J.
Abstract: Introduction: Arresten and canstatin are endogenous anti-angiogenic factors derived from type IV collagen α-chains COL4A1 and COL4A2 respectively. While their functions are explored in cancer studies, little is known about their role in pregnancy. Pre-eclampsia (PE) is a common, serious hypertensive disorder of pregnancy that is characterised by systemic endothelial dysfunction. COL4A1 and COL4A2 are maternal PE susceptibility genes that have increased mRNA expression in PE decidua. Our study aim was to determine the levels of arresten and canstatin in plasma and decidua from PE and gestational age matched normotensive patients. Methods: Plasma was collected from normotensive (n = 44) and PE (n = 39) women during the second and third trimesters of pregnancy. Third trimester decidua was collected at delivery from normotensive and PE women (n = 4 each). Levels of arresten and canstatin were determined by Western immunoblotting. Results: Arresten levels were significantly increased in second and third trimester PE plasma, and in third trimester PE decidua (p < 0.05). Third trimester PE plasma arresten levels also significantly correlated with the need for MgSO4 treatment, where a 1.7 fold increase was observed in patients requiring MgSO4 treatment (p < 0.05). No significant change in canstatin levels was observed between normotensive and PE patients. Discussion: This is the first study to report significant increases in the levels of collagen fragment arresten in PE plasma and decidua. Given its significant increase before the onset of clinical disease and associations with clinical severity in the third trimester, arresten may be a useful biomarker for predicting PE and monitoring its severity. Highlights: Anti-angiogenic type IV collagen fragments arresten is significantly increased in pre-eclamptic plasma. Increases in plasma seen before the onset of pre-eclampsia from 16 weeks' gestation. Increased arresten levels are associated with greater disease severity. Maternal decidua may be a source of these collagen fragments.